2016
DOI: 10.1097/mph.0000000000000488
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Oncology Providers’ Attitudes and Practice Patterns Regarding Fertility Preservation in Adolescent Male Cancer Patients

Abstract: Background The aim of this study was to evaluate pediatric oncology providers’ attitudes toward fertility preservation (FP), their use of educational materials, their approach to FP discussion, and their FP knowledge specifically pertaining to adolescent males. Methods A 40-item online survey was distributed to physicians, advanced practice nurses (APN), and nurses within pediatric oncology. Results About 78.7% of physicians, 81.4% of APN, and 51.9% of nurses reported high levels of comfort in discussing F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 45 publications
(54 citation statements)
references
References 27 publications
2
51
1
Order By: Relevance
“…Four studies reported on clinicians' use of written materials when informing patients of fertility or fertility preservation . Half of physicians and advanced practice nurses reported using fertility educational materials “usually” to “always”; however, the adult language, adult content, and overall reading level were a shortcoming of this material when supplied to young patients of reproductive age . A second study reported that only 13.6% of oncologists “always” to “often” give patients educational materials about fertility preservation, while the majority (60.2%) reported “rarely” to “never” providing written materials .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Four studies reported on clinicians' use of written materials when informing patients of fertility or fertility preservation . Half of physicians and advanced practice nurses reported using fertility educational materials “usually” to “always”; however, the adult language, adult content, and overall reading level were a shortcoming of this material when supplied to young patients of reproductive age . A second study reported that only 13.6% of oncologists “always” to “often” give patients educational materials about fertility preservation, while the majority (60.2%) reported “rarely” to “never” providing written materials .…”
Section: Resultsmentioning
confidence: 99%
“…Clinicians will always discuss fertility with an adolescent, even when parents show doubt or when parents refuse to give permission, and sometimes clinicians talk to adolescents alone without parent's knowledge . Almost all physicians (93%), advanced practice nurses (75%), and half of nurses (48%) reported discussing the impact of cancer treatment on future fertility with adolescent male patients “usually” to “always.”…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations